Developmental Times of Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) at Constant Temperatures and Applications in Forensic Entomology1. Issue 5 (1st September 2016) - Yang, Yong‐qiang; Li, Xue‐bo; Shao, Ru‐yue; Lyu, Zhou; Li, Hong‐wei; Li, Gen‐ping; Xu, Lyu‐zi; Wan, Li‐hua
Abstract: The characteristic life stages of infesting blowflies (Calliphoridae) such as Chrysomya megacephala (Fabricius) are powerful evidence for estimating the death time of a corpse, but an established reference of developmental times for local blowfly species is required. We determined the developmental rates of C . megacephala from southwest China at seven constant temperatures (16–34°C). Isomegalen and isomorphen diagrams were constructed based on the larval length and time for each developmental event (first ecdysis, second ecdysis, wandering, pupariation, and eclosion), at each temperature. A thermal summation model was constructed by estimating the developmental threshold temperature D 0 and the thermal summation constant K . The thermal summation model indicated that, for complete development from egg hatching to eclosion, D 0 = 9.07 ± 0.54°C and K = 3991.07 ± 187.26 h °C. This reference can increase the accuracy of estimations of postmortem intervals in China by predicting the growth of C . megacephala .